Electricity and magnetism in biological systems - Edmonds, D. T (Oxford University Press, 2001)
On the molecular biological level the only significant forces are electromagnetic, so that ultimately all living processes must be understood in terms of electromagnetic fields and forces. The first half of the present book deals with the theory of electromagnetism using a descriptive and geometrical approach suited to students of biology, chemistry, and biochemistry, including biologically relevant examples where possible. The second half contains biological topics which can serve as applications of the theory for students of chemistry or biology, or as an introduction to biology for students trained in the physical sciences who wish to migrate to biology. Topics include the properties of water and ions in bulk solution and in narrow pores, the Debye Layer, possible mechanisms for a magnetic animal compass, an electrostatic model of a proton/ion counterport, and the semi-classical theory of nuclear magnetic resonance.
Keywords: elektřina; Electricity; Biological Science Disciplines; magnetismus; biologické vědy; biologie; Magnetics; přírodní vědy